Impact of Employee Satisfaction and Retention Towards Organizational Performance in the Service Industry - Nur Ilyana Ismarau Tajuddin; Nurfaradilla Haron; Nor Aziyatul Izni; Aeshah Mohd Ali; Nor Asiah Mahmood; Chai Hui Min; Chen Qiyen (Jana Publication and Research, 2024)
Non-Indexed Publication